The Formulation for Translating English-Arabic Words and Terms from The Perspective of Muḥammad ʻInânî - Fauzi, Fajrin (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2025)
This study aims to find out the thoughts of Muhammad ʻInânî in the science of translation and translators and formulate Muhammad ʻInânî's method in English-Arabic translation. This research approach is qualitative. The research method used in this research is a character study. The data collection method used is a literature study. The data processing procedures used are data collection, data selection, data interpretation, and concluding. The conclusion of this research is Muḥammad ʻInânî argues that there are four things that need attention. First, abstract words or terms that are general in nature need attention. Some words are similar to this word, but one word can translate it into Arabic. 2) Second, modern abstract words or terms. He argues that a translator must keep abreast of developments in the formation of new terms in Arabic. He asserts that taulîd or ta'rîb, as well as concrete words or terms, could lead to the formation of this new term. Difficulties occur when translating something of the same type but with a different variety. He explained that to translate this word, the translator can add words that are the special characteristics of the variety. 4) abbreviation. ʻInânî explained that there are two steps when asked to translate abbreviations. First, he must know what abbreviations and acronyms mean. Second, he must know what translations are agreed upon by the international translation group.